Blood-brain transfer of Pittsburgh compound B in humans - Gjedde, Albert; Aanerud, Joel; Braendgaard, Hans; Rodell, Anders B. (Frontiers in Aging Neuroscience, 2013)
In the labeled form, the Pittsburgh compound B (2-(4’-N-methyl-[11C]methyl-aminophenyl)-6-hydroxybenzothiazole, [11C]PiB), is used as a biomarker for positron emission tomography (PET) of brain □-amyloid deposition in Alzheimer’s disease (AD). The permeability of [11C]PiB in the blood-brain barrier is held to be high but the permeability-surface area product and extraction fractions in patients or healthy volunteers are not known. We used PET to determine the clearance associated with the unidrectional blood-brain transfer of [11C]PiB and the corresponding cerebral blood flow rates in frontal lobe, whole cerebral cortex, and cerebellum of patients with Alzheimer’s disease and healthy volunteers. Regional cerebral blood flow rates differed significantly between the two groups, but regional and whole-brain permeability-surface area products were identical, in agreement with the observation that numerically, but insignificantly, unidirectional blood-brain clearances are lower and extraction fractions higher in the patients. The evidence of unchanged permeability-surface area products in the patients implies that blood flow changes can be deduced from the unidirectional blood-brain clearances of [11C]PiB in the patients.